MSC Therapies for COVID-19: Importance of Patient Coagulopathy, Thromboprophylaxis, Cell Product Quality and Mode of Delivery for Treatment Safety and Efficacy - Moll, Guido; Drzeniek, Norman; Kamhieh-Milz, Julian; Geissler, Sven; Volk, Hans-Dieter; Reinke, Petra (Frontiers in Immunology, 2020)
Integrating adaptive and innate immune compatibility testing into the guidelines for cell, tissue and organ transplantation is paramount for safe and effective therapies. There is an urgent clinical need for new guidelines on hemocompatibility testing of intravascular (IV) cellular therapeutics, in particular mesenchymal stromal cells (MSCs). IV-MSCs account for half of all registered MSC-trials and are now in growing demand as potential treatment for coronavirus-induced disease (COVID-19). No approved treatment for COVID-19 exists, but early-phase trials employing MSCs for acute respiratory distress syndrome (ARDS) have shown first promising results and numerous trials to test MSC-infusions as novel treatment for COVID-19 have been registered in the past months. While the need for MSC therapy in COVID-19 is apparent, essential considerations on product quality, safety and efficacy appear to have once more stepped back in favor of fast availability of a potential new treatment. First clinical reports indicate that many COVID-19 patients have a substantially elevated risk for adverse thrombotic events. Infusions of poorly characterized MSC products carry a risk for (lethal) adverse thrombotic reactions due to expression of highly procoagulant tissue factor (TF/CD142), compromising the cells’ hemocompatibility. We here propose new clinical guidelines to mitigate the risk for patients: 1) Updated Clinical Guidelines for Cell and Tissue Transplantation, 2) Updated Minimal Criteria for Characterization of Cellular Therapeutics, and 3) Updated Cell Therapy Routines Reflecting the Specific Patient Needs.